Standardized definitions of molecular response in chronic myeloid leukemia - Cross, Nicholas C. P.; Müller, Martin Christian (Leukemia, 2012)
The International Randomized Study of Interferon and STI571 (IRIS) demonstrated long-term cytogenetic responses in patients with chronic-phase chronic myeloid leukemia (CML-CP) treated with the tyrosine kinase inhibitor (TKI) imatinib. However, deep molecular responses (MRs), as measured by reductions in BCR-ABL transcript levels below the threshold of major MR, were achieved only by a small proportion of patients. With the advent of the second-generation TKIs nilotinib and dasatinib for the treatment of patients with newly diagnosed CML-CP, the proportion of patients who achieve the deepest levels of MR is likely to increase significantly. With these changes, the potential for patient eligibility in TKI cessations studies is becoming a more widely discussed topic and area for research. These developments highlight the need for robust, standardized and workable definitions of deep MRs. Specifically, it is critical that the measurement of MR is standardized in a manner to withstand both intra- and inter-laboratory variability, as well as new methodological developments. This review summarizes the relevant clinical background and proposes a framework within which standardization of MR can be taken forward.
Gesehen am 07.11.2018